2009
DOI: 10.1016/j.otohns.2008.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged vestibular aqueduct in pediatric sensorineural hearing loss

Abstract: Objective Comparison of the Cincinnati criteria (midpoint >0.9 mm or operculum >1.9 mm) to the Valvassori criterion (midpoint ≥ 1.5 mm) for enlarged vestibular aqueduct (EVA) in pediatric cochlear implant patients. Study Design Cohort study Subjects 130 Pediatric cochlear implant recipients. Methods We reviewed temporal bone CT scans to measure the vestibular aqueduct midpoint and opercular width. Results The Cincinnati criteria identified 44% of patients with EVA versus 16% with the Valvassori criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…In 1978, Valvassori and Clemis (75) were the first to describe an associa tion between sensorineural hearing loss and LVA, diagnosed at polytomography, and coined the term "large vestibular aqueduct syndrome" to describe chil dren with LVA and sensorineural hear ing loss that is frequently progressive. Symptoms of vestibular disturbance may also occur as part of this syndrome (76). Multiple studies since then using CT as the imaging modality have esti mated the prevalence of LVA among pa tients with sensorineural hearing loss to be anywhere from 0.64% to 32% (77).…”
Section: Figure 30mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1978, Valvassori and Clemis (75) were the first to describe an associa tion between sensorineural hearing loss and LVA, diagnosed at polytomography, and coined the term "large vestibular aqueduct syndrome" to describe chil dren with LVA and sensorineural hear ing loss that is frequently progressive. Symptoms of vestibular disturbance may also occur as part of this syndrome (76). Multiple studies since then using CT as the imaging modality have esti mated the prevalence of LVA among pa tients with sensorineural hearing loss to be anywhere from 0.64% to 32% (77).…”
Section: Figure 30mentioning
confidence: 99%
“…Highspatialresolution CT is the traditional workhorse, but each modality has relative strengths (76). MR imaging has the advantage of delin eating cranial nerves, including the co chlear nerve, and can offer some infor mation on bony structures such as the otic capsule and vestibular aqueduct based on the contour of the fluid within them.…”
Section: Figure 30mentioning
confidence: 99%
“…28 Regardless of whether the Cincinnati or Valvassori criteria were used for that study in the aggregate analysis, the composite data showed similar results.…”
Section: Resultsmentioning
confidence: 84%
“…In the case where more than 1 system was used to evaluate a single diagnosis in the same subset of patients, the system that the authors espoused in conclusion was used in the analysis. 28 …”
Section: Methodsmentioning
confidence: 99%
“…Enlargement of vestibular aqueduct is defined by criteria established originally by Valvassori and Clemens (2) and further revised in recent years by the Cincinnati group (3). In direct comparison to the Valvassori criterion (midpoint 1.5 mm), Cincinnati criteria (midpoint 0.9 mm or operculum 1.9 mm) identify a larger proportion of pediatric patients with EVA who otherwise have no known etiology of hearing loss (4). EVA can occur as isolated anomaly or can be associated with incomplete partition defects, most commonly IP-II (Classic Mondini deformity).…”
mentioning
confidence: 99%